The Effect Of Multiball Training Methods On Forehand Ability In The Squash Game Of UNM FIK Students - Irvan (Journal Physical Health Recreation (JPHR), 2023)
This research aims to determine the effect of the multiball training method in improving forehand ability in the game of squash. The sample for this research was 35 FIK UNM students using purposive sampling technique. The data analysis technique used is t test analysis with a significance level of α = 0.05. The results of data analysis show a mean value of -11,000, the df value obtained is a value (df) of 14 with a ttable value = 2,145 or smaller than the tcount value = 65,077, and the Sig. of 0.000 or smaller than 0.05. So it can be concluded that the multiball training method can improve forehand ability in squash.